2021
DOI: 10.20535/2410-8286.228211
|View full text |Cite
|
Sign up to set email alerts
|

Newly Qualified Foreign Language Teachers’ Adaptation in Profession: Challenges, Problems, First Achievements and Further Prospects

Abstract: Ukrainian reforms in higher education and participation of universities in different international programmes open new perspectives for quality assurance rising. This study focuses on the foreign language teachers’ professional readiness during their initial period of work and provides an important opportunity to advance the understanding of the main changes in education and their influence on newly qualified FL teachers’ adaptation in the profession. The concept of “foreign language teachers’ training” is stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The tendency concerned about the need of newly-qualified teachers' support approved by the latest research results. According to the research investigated by Komar O. et. al.…”
Section: Figure 1 Survey Diagram With the Data On The Students' Methodology Course Expectationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tendency concerned about the need of newly-qualified teachers' support approved by the latest research results. According to the research investigated by Komar O. et. al.…”
Section: Figure 1 Survey Diagram With the Data On The Students' Methodology Course Expectationsmentioning
confidence: 99%
“…One study by Andrusiak (2017) reports the main positive features and issues relating to the implementation of the "New Generation School Teacher" project within the context of Uzhhorod National University (English Philology department) and proved that the Project has had a favourable impact on teaching practices of the whole department. The other study by Konovalenko, Goncharova (2019) involved the description of new principles and main points of the project "New generation school teacher" and pointed on the importance of its implementation in modern EFL teacher training program at universities. Supporting their ideas, we are aimed to depict Uman State Pedagogical University experience of implementing this project.…”
Section: ключові слова: тенденції програми британської ради англійська мова як іноземна курс підготовки вчителів освітні реформиmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into characteristics of effective FL teachers in the USA was undertaken by Bell (2005), Brown (2009), to name just a few. Challenges and best practices of newly qualified FL teachers in Ukraine were studied by Komar et al (2021). Rigorous research into attributes of effective FL teachers as ascribed by pre-service and inservice teachers in Ukraine could not be located.…”
Section: Introductionmentioning
confidence: 99%
“…A little amount of literature has been published on challenges to education during the war in Ukraine. Recently, a number of studies have shown different ways of managing the education process during pandemics [5], [6], [7]. Several studies investigating education during the Russian invasion have been carried out.…”
mentioning
confidence: 99%